Pseudogymnoascus destructans environmental reservoir decreases 11 years after an outbreak of white‐nose syndrome - Karen J. Vanderwolf; Donald F. McAlpine; Caleb C. Ryan; Hugh G. Broders (Ecosphere)
Abstract White‐nose syndrome is a skin disease of bats caused by the fungus Pseudogymnoascus destructans (Pd). Pd has devastated populations of some bat species in North America, where environmental reservoirs of the fungus are considered a threat to the persistence of bat populations. However, long‐term patterns of Pd environmental persistence in North American hibernacula are unknown. We swabbed hibernacula walls 11 years after the invasion of Pd into Maritime Canada in 2011. This is the first study to examine the persistence of Pd in North American hibernacula >7 years after the first documentation of Pd at a site. The proportion of hibernacula wall swabs with viable Pd decreased over time, with 40.6% of wall swabs positive (n = 32) in 2012, 35.0% (n = 40) in 2015, and 1.7% (n = 120) in 2022. In early winter 2022, 41.18% (n = 17) of bats (Myotis lucifugus, M. septentrionalis, and Perimyotis subflavus) were Pd‐positive compared to 6.67% (n = 15) in late winter, a low prevalence and the opposite pattern compared to the first 4 years after Pd invasion to sites. Our results suggest that Pd loads in the environment naturally decrease to low or undetectable levels over time in our study region. Since attempts to reduce environmental reservoirs have a high likelihood of negative nontarget effects on hibernacula ecosystems, and a low likelihood of completely eradicating Pd, actions to reduce environmental reservoirs in hibernacula should consider deprioritizing sites where Pd has been present >10 years. We urge the collection of further data across hibernacula sites with varied geochemistry, microclimates, organic matter availability, timing of Pd arrival, and surviving bat colony sizes. This will allow a more comprehensive assessment of this strategy.